The Teacher Written Corrective Feedback Practices in EFL Writing Classroom - Dyah Fitri Mulati; Joko Nurkamto; Nur Arifah Drajati (IJER (Indonesian Journal of Educational Research), 2018)
[Understanding Teacher Written Corrective Feedback Practices in EFL Writing Classroom] Feedback is widely applied as the scaffolding learning techniques in the field of second and foreign language writing. This significance has also been recognised as a form of the students’ improving control over composing skills key element that is acknowledged as the process-based classroom. However, there is less published literature about how secondary teacher in EFL context responds to the students’ writing. Further, little is known about why teachers respond the writing in the ways they do, and the factors behind the current feedback practices. Therefore, this study addressee the tensions in the written corrective feedback type and strategy applied at a secondary school involving a teacher as its participant. It was designed as a case study aiming at (1) examining the actual feedback practice and its reason, (2) describing factors that shape teacher’s current practice in providing written corrective feedback. The data were gathered by document analysis and using interview adapted from Lee (2009) consisting of five items related to the actual practices in written corrective feedback type and strategy, followed by factors that shape those practices. The findings showed that teacher was favoured to use indirect, uncoded, hints and selective written corrective feedback. In addition, two factors were found taking the responsibility of those current practices.